The interventions of the European Central Bank: Effects, effectiveness, and policy implications - Michael Frenkel; Georg Stadtmann; Christian Pierdzioch (Deutsche Bank Research, 2001)
We analyze the effectiveness of the foreign exchange market interventions conducted by the European Central Bank (ECB) in the fall of 2000 to support the external stability of the euro. To this end, in a first step different channels through which interventions may influence exchange rate dynamics are discussed. In a second step, a review of the existing empirical literature on the effectiveness of central bank interventions is used as the basis for evaluating the effectiveness of the ECB's intervention policy. Against this background, high-frequency exchange-rate data are used to examine the effects of the interventions. We present evidence that the interventions only had a very short-term impact on the exchange rate path with no medium-term effects. All in all, our results suggest that the ECB's intervention policy was not effective.
Keywords: F31; 330; European Central Bank; Foreign exchange market interventions; Wechselkurspolitik; Wirkungsanalyse; Europäische Wirtschafts- und Währungsunion; Wechselkurs; EU-Staaten